2015
DOI: 10.19030/ajee.v6i2.9502
|View full text |Cite
|
Sign up to set email alerts
|

Developing An Engineering Identity In Early Childhood

Abstract: This project describes a strategy to introduce young children to engineering in a way that develops their engineering identity. The targeted age group is 3-7 year old students because they rarely experience purposeful engineering instruction. The curriculum was designed around an engineering storybook and included interactive academic discussions as well as a creative drawing activity. Results provide evidence that students developed an engineering identity based on their illustrations of themselves working as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 14 publications
1
31
0
7
Order By: Relevance
“…Finally, teaching engineering also includes helping students see themselves as engineers. Studies have shown that helping students identify as engineers increased their views of who can be engineers (Capobianco et al, 2011;Pantoya, Aguirre-Munoz, & Hunt, 2015). Furthermore, in a first-year engineering program, Lindsay, Munt, Rogers, Scott, and Sullivan (2008) purposefully designated and treated their students as "student engineers" rather than "engineering students" to help them gain the skills of practicing engineers.…”
Section: Teaching Engineeringmentioning
confidence: 99%
“…Finally, teaching engineering also includes helping students see themselves as engineers. Studies have shown that helping students identify as engineers increased their views of who can be engineers (Capobianco et al, 2011;Pantoya, Aguirre-Munoz, & Hunt, 2015). Furthermore, in a first-year engineering program, Lindsay, Munt, Rogers, Scott, and Sullivan (2008) purposefully designated and treated their students as "student engineers" rather than "engineering students" to help them gain the skills of practicing engineers.…”
Section: Teaching Engineeringmentioning
confidence: 99%
“…However, such experiences are not uncommon in early childhood research. While there is a consensus among pre-primary researchers that children come to school with sufficient knowledge about the natural world (Pantoya, Aguirre-Munoz, and Hunt, 2015;Shonkoff and Phillips, 2000), can abstractly and concretely think (IOM and NRC, 2015), but the early technology and engineering realms are less understood and taught (National Association for the Education of Young Children [NAEYC] and Fred Rogers Center for Early Learning and Children's Media, 2012;Pantoya et al, 2015). This may be due to misconceptions among many pre-primary stakeholders that engineering and technology as subjects at pre-primary levelmeans using digital and/or electronic technology, such as touch-screen tablets and construction of block buildings and bridges in a classroom.…”
Section: Teachers' Experiences In Teaching and Learning Of Stem At Prmentioning
confidence: 99%
“…Positive shifts in interest have been observed internationally when incorporating engineering projects into secondary schools (Malone, Schuchardt and Schunn, 2018) and informal outreach programs to K12 schools (Johnson et al, 2013;Karp and Maloney, 2013;Shahali et al, 2017). The incorporation of engineering at the early elementary school level (students five to 10 years old) has included the use of engineering picture and trade books to introduce engineering challenges (Milto et al, 2016;Pantoya et al, 2015), engineering design projects (Lachapelle and Cunningham, 2014;Silver and Rushton, 2008b), and animated videos (Johnson et al, 2013). The lack of inclination to become an engineer may be caused by the negative stereotypical images held by students rather than enjoyment of science and engineering (Silver and Rushton, 2008a;Wang and Degol, 2017).…”
Section: Introductionmentioning
confidence: 99%